Peripapillary microvasculature in the retinal nerve fiber layer in glaucoma by optical coherence tomography angiography: focal structural and functional correlations and diagnostic performance - Richter GM (Dove Medical Press, 2018)
Grace M Richter,1,* Beau Sylvester,1,* Zhongdi Chu,2 Bruce Burkemper,1 Ingy Madi,1 Ryuna Chang,1 Alena Reznik,1 Rohit Varma,1 Ruikang K Wang2 1Department of Ophthalmology, USC Roski Eye Institute, Keck School of Medicine of University of Southern California, Los Angeles, CA, USA; 2Department of Bioengineering, University of Washington, Seattle, WA, USA *These authors contributed equally to this work Purpose: To quantify peripapillary microvasculature within the retinal nerve fiber layer (RNFL) in primary open-angle glaucoma (POAG) and normal eyes, determine association of perfusion parameters with structural and functional measures, and report diagnostic accuracy of perfusion parameters.Patients and methods: POAG and normal patients underwent 6×6 mm2 optic nerve head scans (Angioplex optical coherence tomography angiography [OCTA]; Cirrus HD-OCT 5000) and Humphrey Field Analyzer II-i 24-2 visual field (VF) testing. Prototype software performed semiautomatic segmentation to create RNFL en face images and quantified vessel area density (VAD), vessel skeleton density (VSD), and vessel complexity index (VCI) in the optic nerve head globally and focally. Generalized estimating equations models assessed association of OCTA parameters with VF mean deviation (MD) and RNFL thickness.Results: Thirty-eight POAG and 17 normal eyes were studied. Global VAD, VSD, and VCI were reduced in mild POAG vs normal (P<0.02) and moderate-severe vs mild POAG (P<0.04). Stepwise focal reductions across disease stage were demonstrated for OCTA parameters in the inferior hemisphere (P<0.05); reduction in OCTA parameters in mild POAG vs normal was demonstrated in inferior and superior quadrants (P<0.05). Reduced global VF MD was associated with reduced VAD, VSD, and VCI (P=0.0007, 0.0013, <0.0001; R2=0.449, 0.312, 0.399, respectively), and global RNFL thickness was associated with VAD, VSD, and VCI (P<0.0001; R2=0.499, 0.524, 0.542), superior and inferior hemifield MD were associated with corresponding VAD, VSD, and VCI (P≤0.001; R2 from 0.208 to 0.513). RNFL thickness in all quadrants was associated with corresponding OCTA parameters (P<0.05; R2 from 0.213 to 0.394), except temporal VAD and VCI. Area under curves for VAD, VSD, and VCI demonstrated good diagnostic ability (0.868, 0.855, 0.868; P<0.0001).Conclusion: Glaucomatous eyes showed stepwise reductions in RNFL microcirculation across severity; focal reductions in the inferior hemisphere and inferior and superior quadrants were most significant. OCTA parameters had stronger associations with structural rather than functional measures of glaucoma. Keywords: optic nerve head, segmentation, large vessel subtraction, structure, function, microcirculation, diagnostic accuracy